Investigations on some microbiological and chemical features of "Kurut" - Patir, Bahri; Ateş, Gülsüm (My University, 2002)
The microbiological and chemical qualities of kurut, which is made from dried yoghurt with solar heat in some rural regions of Anatolia, were studied. For this aim 25 kurut samples from the Elazi? area were investigated. Colony forming units of mesophile aerobes, coliform, Staphylococcus-Micrococcus, Lactobacillus-Leuconostoc-Pediococcus, Lactococcus, yeast and mould on average were 3.40 × 104/g, 2.79 × 102/g, 2.40 × 103/g, 2.23 × 104/g, 1.13 × 104/g and 1.12 × 104/g respectively. Twelve percent of samples contained Escherichia coli 1, and 16% had Staphylococcus aureus microorganisms. The pH, acidity (as lactic acid), moisture, fat, fat content of dried matter, salinity, salt content of dried matter and ash of the samples on average were 4.26, 2.40%, 10.96%, 32.90%, 37.14%, 12.85%, 14.41% and 11.79% respectively. The correlation between the general mesophile aerobe counts and dry matter were negative and strong (r = -0.84). These correlations for Lactobacillus-Leuconostoc-Pediococcus, Lactococcus and yeast and mould microorganisms were, r = -0.82, r = -0.81 and r = -0.83 respectively. In addition, the correlation between coliform group microorganisms and NaCl was found to be negative (r = -0.51), and Staphylococcus-Micrococcus microorganisms were positive (r = 0.62) and moderate. It is concluded that, kurut contained considerable amounts of pathogen microorganisms such as Escherichia coli 1 and Staphylococcus aureus, and was prepared and stored under unhygienic conditions. Chemical analysis shows that kurut has low moisture but very high fat, salt and ash contents.
Kurut un mikrobiyolojik ve kimyasal bazi nitelikleri üzerine araştirmalar
Keywords: Chemical; Feature; Kurut; Microbiological